(untitled) (Journal of Economic Research & Business Administration, 2015)
Role internal control in managerial system activity insurance subject exploratory considerably tight sphere specialist, nay one from central failure discuss and solve roadblock appear local makeup their investigation, that ultimately clampdown full development and improvement internal control in managerial system insurance business. Show interrelation internal control with book records, also consist in academic substantiation, working question internal control in insurance company.In accounting controls legality accomplish activity, correctness appearance basic document and bargain and only by good position discounting possibility appreciation and overpayment in two ups fruition absorbed expenses. At management accounting control primarily aim on perspective. Under administration materialize action on elimination arise deviation and attainment fix goal